Managerial Categorization of Competitors: Using Old Maps to Navigate New Environments - Reger, Rhonda K.; Palmer, Timothy B. (Organization Science, 1996)
The authors empirically examine differences between automatic and controlled processing by executives in an increasingly dynamic industry. The results suggest that cognitive inertia affects judgments in both modes, but the effect is stronger with automatic processing. Specifically, the authors conducted two studies examining executives' cognitive maps of competitive positioning. First, they explored differences in ways strategists categorize competitors in a cross-sectional field study conducted during a period of significant environmental upheaval. They found that managers relied on cognitive maps that reflected obsolete industry boundaries rather than configurations representative of the deregulated marketplace. Hence, managers must be mindful to incorporate new information proactively from many sources and to actively discard old, automatic maps in order to develop reliable maps for changing environments. In a second study, managerial competitive schemas of competitive positioning were compared longitudinally across three research projects conducted in the financial intermediary industry. An eight-year time frame provided a unique opportunity to explore the content of mental models in an industry undergoing an accelerating rate of change. The longitudinal results indicate that change creates diversity of thought across managers in the same environment. Managers at competing firms are therefore apt to view competition quite differently in turbulent environments. Implications of the study findings for strategic decision making, consensus and conflict, and organizational learning and executive succession in turbulent environments are discussed. Issues are identified that warrant further research.